World-Weariness and Augustine’s Eschatological Ordering of Emotions in enarratio in Psalmum 36 - Stewart-Kroeker, Sarah (Augustinian studies, 2016)
Augustine’s homiletical exhortations display a strong eschatological emphasis in his approach to cultivating rightly ordered emotions. According to critics such as Hannah Arendt, Martha Nussbaum, and Thomas Dixon, this orientation risks denigrating the earthly life and its attendant emotions, while also promoting a crippling resignation to suffering. This article discusses Augustine’s eschatological frame for ordering the emotions through a focused treatment of en. Ps. 36 (particularly the first homily) in conversation with Nussbaum’s critique in particular. In en. Ps. 36.1, Augustine deploys eschatological rhetoric to discourage the believer’s envious response to a prosperous, profligate neighbor. This entails disposing the believer in weariness toward life’s temporal disparities and exhorting the believer to work in love to alleviate suffering with a view to heavenly flourishing. In this sense, a disposition of "world-weariness" works in concert with eschatological hope to rightly order both emotion and action in this present world.